DINS : a distributed scheme for sensor fusion over fading channels - Zhu, Shanying (2018)
In this paper, we consider the problem of distributed sensor fusion in relay-assisted sensor networks with time-varying asymmetric communications over fading channels. A Distributed INnovation based Scheme (DINS) is proposed by fusing both the local measurements and the information received from neighboring nodes. We present a hybrid TDMA scheme for efficient implementation of DINS and the design of parameters of DINS to bring the effects of fading under a satisfactory level. With an appropriate design, it is shown that our algorithm is able to produce estimates with desired asymptotic properties of unbiasedness and consistency. Simulation results are provided to demonstrate the performance of DINS.